PEMBINAAN BATIK PONOROGO - FP. Sri Wuryani (Institut Seni Indonesia Surakarta, 2020)
Senior High School I (SMAN I) Ponorogo is an education institution that gives appreciation towards batik training. The activity aims to produce a batik motive design which one of them can be used as the uniform. Motive of batik uniform can presents symbolic values in accordance to the local character of Ponorogo and the character of correlated institution as well. By using tutorial and practical method, there can be produced some batik motives which one of them can be used as the uniform of SMAN I Ponorogo.Keywords: motive, design, batik, Ponorogo.